Aerosolization of Crude Oil‐Dispersant Slicks Due to Bubble Bursting. Issue 10 (24th May 2019) - Sampath, Kaushik; Afshar‐Mohajer, Nima; Chandrala, Lakshmana D.; Heo, Won‐Seok; Gilbert, Joshua; Austin, David; Koehler, Kirsten; Katz, Joseph
Abstract: Bubble bursting is a primary source of marine aerosols, yet little is known about particle emissions due to the bubble bursting in slicks containing oil‐dispersant mixtures. In this study, bubbles with mode sizes of 86 μm (denoted as small), 178 μm (medium), and 595 μm (large) are injected into a seawater column covered by slicks of crude oil, pure dispersant, and dispersant premixed with oil at a ratio of 1:25. The aerosol size distributions are monitored in the 0.5‐ to 20‐μm and 10‐ to 380‐nm ranges both in clean and ambient air environments. In ambient air, a tenfold increase in submicron particle concentration occurs when large bubbles burst on slicks of 500‐μm dispersant premixed with oil at a ratio of 1:25 oil or 50‐μm pure dispersant. Yet, in multiple tests performed at different ambient particle concentrations, the elevated size distributions persistently maintain the same shape as that of the ambient air. In contrast, smaller bubbles and tests not involving dispersants do not cause such an increase. Nanodroplets are also generated by large bubbles in particle‐free air, but their concentrations are much lower. All plumes generate micron‐sized aerosols, but trends vary. For the same contaminant, the microdroplet concentration decreases with increasing slick thickness. Particularly striking is a reduction of 2 orders of magnitude in the microdroplet concentration when medium and small bubbles burst on 500‐μm crude oil slicks. Chemical analysis of air and particulates collected from filters sampling the particles confirms the presence of airborne oil above the slicks. Key Points: Bursting of bubbles in slicks containing crude oil and dispersant mixtures aerosolizes the oil, generating microdroplets and nanodroplets In ambient air, a tenfold increase in submicron particle concentration occurs when large bubbles burst on slicks containing dispersants Microdroplets are generated for all bubble plumes and slick types, but their concentration decreases with increasing slick thickness